Handbook of land and water grabs in Africa foreign direct investment and food and water security - edited by Tony, Allan (New York Routledge, 2013)
According to estimates by the International Land Coalition based at the International Fund for Agricultural Development (IFAD), 57 million hectares of land have been leased to foreign investors since 2007. Current research has focused on human rights issues related to inward investment in land but has been ignorant of water resource issues and the challenges of managing scarce water. This handbook will be the first to address inward investment in land and its impact on water resources in Africa.
Includes bibliographical references and index.
Keywords: Investments, Foreign--Africa.